2015
DOI: 10.1038/srep16798
|View full text |Cite
|
Sign up to set email alerts
|

Bioinspired Breathable Architecture for Water Harvesting

Abstract: Thuja plicata is a coniferous tree which displays remarkable water channelling properties. In this article, an easily fabricated mesh inspired by the hierarchical macro surface structure of Thuja plicata branchlets is described which emulates this efficient water collection behaviour. The key parameters are shown to be the pore size, pore angle, mesh rotation, tilt angle (branch droop) and layering (branch overlap). Envisaged societal applications include water harvesting and low cost breathable architecture f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 5 publications
0
7
0
Order By: Relevance
“…Waterproof and breathable functional membranes designed for coats should possess three main characteristics: materials should be water repellent, water vapor permeable, and wind resistant. Apart from water repellency, permeability to water vapor should permit evaporating sweat from the skin’s surface to ensure the wearer feel comfortable; the windproof property prevents cold wind from entering the space between the skin and garments during extreme climate conditions. Sweat vapor breathability and windproofness were usually characterized in terms of WVTR and air transmittance, respectively.…”
Section: Results and Discussionmentioning
confidence: 99%
“…Waterproof and breathable functional membranes designed for coats should possess three main characteristics: materials should be water repellent, water vapor permeable, and wind resistant. Apart from water repellency, permeability to water vapor should permit evaporating sweat from the skin’s surface to ensure the wearer feel comfortable; the windproof property prevents cold wind from entering the space between the skin and garments during extreme climate conditions. Sweat vapor breathability and windproofness were usually characterized in terms of WVTR and air transmittance, respectively.…”
Section: Results and Discussionmentioning
confidence: 99%
“…8 The understanding and replication of such surfaces is paving the way to many everyday technological applications; for example, self-cleaning designs based upon the lotus leaf have been introduced into the paint, glass, automotive, and textile industries. 9 Plant species displaying a range of wettabilities have been widely studied.…”
Section: Introductionmentioning
confidence: 99%
“…Finally, condensates are accumulated on the root of the 1-L. It is different from the water collection mechanism of the porous mesh inspired by Thuja plicata tree, which collects water by capturing the tiny water when the fog passes the porous structure . To exhibit the unidirectional water movement along the tracks, the sample is tested on a cooling horizontal stage by injecting red ink on the 4-L (see Figure a–c and Movie S6).…”
Section: Resultsmentioning
confidence: 99%
“…Some organisms such as Namib Desert beetles and cactuses can adapt to the xeric conditions due to their unique fog-harvesting abilities. , The strategy of water collection imitating these creatures has gained increasing attention. Inspired by Namib Desert beetles, , cactuses, ,, spider silk, nepenthes, Burkheya purpureas, and leaves, numerous bionic structures have been introduced. Parker et al revealed that a near-random array of hydrophilic bumps with superhydrophobic troughs on the elytra of Stenocara resulted in an excellent fog-harvesting ability .…”
Section: Introductionmentioning
confidence: 99%